1995
DOI: 10.1139/y95-192
|View full text |Cite
|
Sign up to set email alerts
|

Evolution off spontaneous activity in the developing rat superior colliculus

Abstract: During the first 10 days after birth in the rat there are a succession of major developmental stages in the retinotectal pathway. During most of this time, the only recordable event in the superior colliculus is spontaneous activity. We studied and characterized this spontaneous activity, hypothesizing that it could play an important role in pathway development. The spontaneous discharges are detectable on postnatal day 5 (P5). After P5, the number of spontaneously active cells per penetration increases up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…For these reasons, we predicted that early light-driven activity in the retina may begin to drive visual neurons of the sSC and initiate the CaN-mediated change. Previous investigations have shown that the photoreceptor-bipolar-ganglion cell pathway is glutamatergic (Itaya et al, 1995;Bansal et al, 2000;Wong et al, 2000). Our data indicate that this pathway can be impaired in the early retina by infiltrating one eye cup with AMPA/KAR and NMDAR antagonists.…”
Section: Discussionsupporting
confidence: 49%
“…For these reasons, we predicted that early light-driven activity in the retina may begin to drive visual neurons of the sSC and initiate the CaN-mediated change. Previous investigations have shown that the photoreceptor-bipolar-ganglion cell pathway is glutamatergic (Itaya et al, 1995;Bansal et al, 2000;Wong et al, 2000). Our data indicate that this pathway can be impaired in the early retina by infiltrating one eye cup with AMPA/KAR and NMDAR antagonists.…”
Section: Discussionsupporting
confidence: 49%
“…In the superficial visual layers of the superior colliculus, synaptogenesis can be studied anatomically (Thong and Dreher, 1986;Warton and McCart, 1989;Contamina and Boada, 1992;Colonnese and Constantine-Paton, 2001) and physiologically (Itaya et al, 1995;Binns and Salt, 1997;Fortin et al, 1999) because of the direct and dominant innervation from the retina and visual cortex and the synchronization of synaptic development (Shi et al, 1997Aamodt et al, 2000). Previously we reported that chronic application of low levels of NMDA to the sSC at P8 upregulates GABA A receptor-mediated synaptic activity at P12, 5 d before this increase would occur during normal development.…”
Section: Discussionmentioning
confidence: 99%
“…SNA is expressed in the spinal cord, retina, hippocampus, brain stem, superior colliculus, and others, shortly after synaptic connections first form, (Gummer and Mark, 1994; Fortin et al, 1995; Itaya et al, 1995; Lippe, 1995; Feller, 1999; Ho and Waite, 1999; O’Donovan, 1999; Wong, 1999; Ben-Ari, 2001). SNA exists as episodic bursts of spiking activity that last for seconds and are followed by longer lasting quiescent periods, as shown in Figure 1 (muscle nerve recordings in chick embryo spinal preparation).…”
Section: Spontaneous Network Activity In Chick Embryo Spinal Circuitrymentioning
confidence: 99%